(untitled) - S.UMA SUBBULAKSHMI, Dr.N.Nirmal kumar, Dr.P.Mehalingam palanichamy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There is the decline of environmental quality due to human action and natural processes. The quality of the environment is degraded due to the erosion of natural ecosystems due to human or natural processes as well as depletion of resources like air, water, soil. According to the United Nations, environmental degradation is the decline in the ability to meet social and ecological goals and needs. There are many nano particles in the environment which has effects in both way i.e. potential positive effects and negative effects. To study about the process involved in the ecosystem, special concern with nano particle is the main aim of current study. The researcher tried to find out the potential effect of nano material on eco-system and the involved process in it.